The Influence of Location, Promotion, and Service Quality on Purchase Interest in Coffee Bento in Cirebon City - Devi Ika Afriani; Hesty Rachma Yanti; Ramlah Puji Astuti (Indonesian Journal of Business Analytics, 2024)
In Indonesia, the habit of drinking coffee has become part of people's lives, and cafes are not only a place to enjoy coffee but also a place for various social and business activities. Although the coffee shop business promises great opportunities, it also faces stiff competition. One of the key factors in winning competition is understanding and fulfilling customer needs and satisfaction. This research aims to determine the relationship between location, advertising, and service quality on customer purchase intentions at Bento Kopi, a cafe in the city of Cirebon. Using quantitative methods, data was collected by distributing questionnaires to 100 respondents selected using purposive sampling. Data analysis was carried out using classical assumption tests, multiple linear regression, and hypothesis testing. The findings show that there is a positive relationship between location, advertising, service quality, and customer purchase intentions. Based on the findings of this research, shows that location, advertising, and service quality simultaneously influence consumer purchasing intentions. This shows that location, advertising, and service quality influence consumer purchasing intentions. This is very important to satisfy the desires of purchasing decisions which until now only represent the interests of consumers.